2014
DOI: 10.1111/jfs.12157
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Domiati Cheese and the Influence of Probiotics on the Behavior of Staphylococcus aureus and Escherichia coliO157:H7 in Domiati Cheese

Abstract: The objectives of this study were to assess the microbiological quality of domiati cheese and to evaluate the capacity of Lactobacillus acidophilus La-5 and Bifidobacterium longum ATCC15707 to inhibit the growth of Staphylococcus aureus and Escherichia coli O157:H7 during manufacture and storage of domiati cheese. The results of the microbial investigation indicated poor microbiological quality of cheese samples, the microbiological parameters recorded higher values than admissible levels. Domiati cheese produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
(52 reference statements)
4
13
0
Order By: Relevance
“…Aly et al (2007) and Meshref and Hassan (2009) found 52.5 and 78 % of the cheese samples were contaminated with coliforms, respectively. El-Kholy et al (2014) explained high counts of coliforms in cheese may occasionally provide an increased risk for early blowing or gassing of the product, which can be observed by large gas holes and a spongy texture of the cheese during the initial days of manufacturing. Presence of high counts of molds and yeasts in cheese can be also related to the unsanitary practices during cheese making, insufficient conditions of utensils, unacceptable controlling of pasteurization process and the use of low-quality milk and ingredients (Coveney et al 1994).…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…Aly et al (2007) and Meshref and Hassan (2009) found 52.5 and 78 % of the cheese samples were contaminated with coliforms, respectively. El-Kholy et al (2014) explained high counts of coliforms in cheese may occasionally provide an increased risk for early blowing or gassing of the product, which can be observed by large gas holes and a spongy texture of the cheese during the initial days of manufacturing. Presence of high counts of molds and yeasts in cheese can be also related to the unsanitary practices during cheese making, insufficient conditions of utensils, unacceptable controlling of pasteurization process and the use of low-quality milk and ingredients (Coveney et al 1994).…”
Section: Microbial Contaminationmentioning
confidence: 99%
“…It was observed that the hygienic quality of most of Domiati cheese, which collected from dairy shops in Egypt, was not met the Egyptian Standard and could be a source of health risk. The publications showed that S. aureus was detected in most Domiati cheese samples, which collected from various dairy shops, street vendors, and supermarkets located in different governorates in Egypt such as Aswan, Gharbia, Beni‐Suef, and Cairo (Eid & Eltalawy, ; El‐Kholy, El‐Shinawy, Meshref, & Korany, ; Ibrahim, Sharaf, & El‐Khalek, ; Malt, ). Although S. aureus was found in raw milk, the presence of S. aureus in Domiati cheese is usually due to unhygienic handling of the product and/or an extensive contamination by personnel possibly involved in cheese during making and marketing (El‐Kholy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The publications showed that S. aureus was detected in most Domiati cheese samples, which collected from various dairy shops, street vendors, and supermarkets located in different governorates in Egypt such as Aswan, Gharbia, Beni‐Suef, and Cairo (Eid & Eltalawy, ; El‐Kholy, El‐Shinawy, Meshref, & Korany, ; Ibrahim, Sharaf, & El‐Khalek, ; Malt, ). Although S. aureus was found in raw milk, the presence of S. aureus in Domiati cheese is usually due to unhygienic handling of the product and/or an extensive contamination by personnel possibly involved in cheese during making and marketing (El‐Kholy et al, ). So the control of S. aureus in Domiati cheese making is an important issue, not only as economic impact for dairy industry but also as significant public health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damietta cheese is the most popular type of pickled soft cheese by all socioeconomic classes in Egypt due to its nutritional value, convenience and good taste. Fully ripened Damietta cheese has strong, sharp flavor, as well as smooth body and texture [ 1 ]. Furthermore, Kareish cheese is considered as one of the most popular local types of fresh soft cheese in Egypt.…”
Section: Introductionmentioning
confidence: 99%